Promoting reflection in pre-service teachers through problem-based learning: an example from Canada. Issue 3 (3rd May 2016) - Koh, Kim; Tan, Charlene
Abstract: This article discusses the process, benefits, challenges and recommendations associated with the adoption of the Problem-based Learning (PBL) approach to promote reflection for pre-service teachers. Drawing upon Schön's concept of reflection, this article explains how a pre-service course in Canada aims to promote the participants' 'reflection in action' of assessment content knowledge and professional competence through PBL. The article points out that PBL enables the pre-service teachers to critically reflect on assessment issues and make meaningful connections between their reflections and real-life teaching. The key challenges are the facilitators' inadequate understanding of using PBL to promote reflection, as well as the pre-service teachers' struggle with time constraint and juggling between their need for teacher guidance, group collaboration and self-directed study. To address these challenges, the article recommends formal professional development sessions for the PBL instructors, and the achievement of a balance between learner autonomy and teacher guidance.